Trade in third and fourth hijri centuries syria - Hassan, Mohamed S. (Humanities Journal of University of Zakho, 2013)
In this period syria was part of a greater Islamic world.it was affected by this world،s political and economical state and the industrial development ،agricultural activity and geographical location had a great effect on the trade development. One to its location ،it has become a bidge for trade between east and west ، which had its impact in the development of its provinces which are located along the caravan routes as well as the coastal cities which have trade harbours .therefore ،alleppo and Damascus became famous for their rich merchandise and also coastal cities such as tripoli،Beirut،syria،sidon and akka which played an essential role in international trade during this period. They were described as cities full of precious goods and strations for trade caravans. Syria has not been merely aroute of trade ،but also played amajor role in that trade trough exporting a number of its productions to neighbouring countries and importing other types of goods.